The Effectiveness of Group Counseling Services Using the Rational-Emotive Imagery (REI) Technique to Enhance Mental Well-Being among University Students - Hasanah, Uswatun; Rusman , Abdul Aziz (Journal of Educational Sciences, 2025)
This study aims to examine the effectiveness of group counseling services using the Rational Emotive Imagery (REI) technique in enhancing the mental well-being of university students. The research employed a quantitative approach with a one-group pretest–posttest design, involving eight students from the Guidance and Counseling Education Program, Class of 2022, who demonstrated low levels of mental well-being. Participants were purposively selected based on pretest results and their willingness to attend all service sessions. The REI technique, which is part of the Rational Emotive Behavior Therapy (REBT) approach, focuses on individuals’ ability to imagine stress-inducing situations and transform irrational beliefs into more rational emotional responses. The findings revealed a significant improvement in the mean scores of mental well-being, increasing from 25.63 (low category) in the pretest to 45.25 (moderate category) in the posttest. The Wilcoxon Signed Ranks Test yielded a significance value of 0.012 (p < 0.05), indicating a meaningful difference between conditions before and after the intervention. These results demonstrate that group counseling services using the REI technique are effective in improving emotional regulation, resilience, and students’ overall mental well-being. Therefore, this technique is recommended for implementation in counseling programs, particularly in higher education, as a strategic intervention to support students’ mental health in coping with academic pressures and campus life challenges.